The Effect of the Tilawah Method on Nagham’s Ability to Recite the Quran - Jannah, Miftahul; Khadijah, Khadijah; Fatia, Azhariah; Sabhamis, Sabhamis; Hayati, Naila (El-Rusyd, 2026)
This study aims to determine the effect of the tilawah method on students’ ability to recite the Quran with proper intonation in the Quran and Hadith course at Islamic educational institutions in Indonesia. This study employs a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The research sample was selected using purposive sampling. Data were collected through an oral test of intonation ability and analyzed using a normality test and a paired-sample t-test with the aid of SPSS. The results indicate that the students’ intonation ability improved after the implementation of the tilawah method, as evidenced by the increase in the mean post-test score compared to the pre-test score. The hypothesis test yielded a significance level (2-tailed) of < 0.05, indicating that the tilawah method has a significant effect on the students’ nagham skills in reciting the Quran. The implications of this study suggest that the tilawah method can be used as an alternative teaching method for the Quran and Hadith to improve students’ nagham skills and the quality of their Quranic recitation.